Proposta de melhoria de uma linha de produção através da aplicação de ferramentas da gestão da produção - Vitorassi, Bruno (2015)
Industries search continuously for ways to eliminate losses from their processes. A focus of waste is the unnecessary displacement caused by inneficient leiautes. Through the application of lean manufacturing tools and principles, it is possible to reduce losses and have a leaner and more focused process on value aggregation. This work aimed the identification and elimination of existing waste in a production line of an automotive industry with the support of lean manufacturing tools, such as Value Stream Mapping, manpower activities balancing and leiaute change. The utilization of these tools made it possible to observe that the main losses were caused by a poor line balancing instead of the leiaute, as supposed initially. The improvement on the manpower balancing enabled the reduction of up to two operators and the respective manpower cost by approximately 30% per year. Although the final proposed leiaute itself did not bring any relevant economic gain, it enabled the implementation of the proposed balancing, an improved flow of material and a better usage of the available area.